Effect of Nitrogen Arc Discharge Plasma Treatment on Physicochemical Properties and Biocompatibility of PLA-Based Scaffolds; Polymers; Vol. 15, iss. 16 - Laput O. A. Olesya Aleksandrovna; Vasenina I. V. Irina Vladimirovna; Korzhova A. G.; Bryuzgina A. A. Anastasia Andreevna; Khomutova U. V. Ulyana Viktorovna; Tuyakova S. G. Sitora Gayratbekovna; Akhmadeev Yu. Kh. Yury Khalyafovich; Shugurov V. V. Vladimir Viktorovich; Bolbasov E. N. Evgeny Nikolaevich; Tverdokhlebov S. I. Sergei Ivanovich; Chernyavsky A. V. Aleksandr Viktorovich; Kurzina I. A. Irina Aleksandrovna (2023, 2023)
Title screen